The Prevalence and Antibiotics Susceptibility Patterns of Corynebacterium minutissimum Isolates from Skin Lesions of Patients with Suspected Erythrasma from Tabriz, Iran. (30th November 2022) - Salemi, Seyedeh Zahra; Memar, Mohammad Yousef; Kafil, Hossein Samadi; Sadeghi, Javid; Ghadim, Hamideh Herizchi; Alamdari, Hamideh Azimi; Nezhadi, Javad; Ghotaslou, Reza
Abstract : Erythrasma is a chronic infection of the skin that appears in the body folds as flat copper spots. The causative agent of this infection is Corynebacterium minutissimum ( C. minutissimum ). Erythrasma can be treated with antiseptics or topical antibiotics. The study aimed to investigate the antibiotics susceptibility patterns, and the presence of the erythromycin resistance gene ( ermX and mefA ) in C. minutissimum isolates in skin lesions with suspected erythrasma. From July 2020 to May 2022, 278 skin scrub specimens were collected from patients admitted to the hospital of Tabriz University of Medical Sciences. Specimens were incubated on the blood agar plates and isolates were identified by microbiological laboratory methods. The antibiotic susceptibility patterns were determined by the disk diffusion method and resistance genes of ermX and mefA were detected by the PCR method. Out of 278 specimens, 41 C. minutissimum isolates (14.74%) were recovered. The highest frequency of resistance was observed to a penicillin (75.6%) followed by erythromycin and clarithromycin (39.02%), clindamycin (30.05%), tetracycline (24.2%), and gentamicin and neomycin (19.5%). The frequencies of ermX and mefA genes were 75% and 12.5%, respectively. Resistance to antimicrobial drugs was common and worrying. Resistance to erythromycin in C. minutissimum is mainly related to the ermX gene.